The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s00027-011-0202-y
|View full text |Cite
|
Sign up to set email alerts
|

Crustacean zooplankton sedimentary remains from calcium-poor lakes: complex responses to threshold concentrations

Abstract: Declines in lakewater calcium (Ca) concentrations are occurring in many softwater lakes of the Canadian Shield, and likely elsewhere, and there is growing interest regarding the potential impacts that reduced Ca availability may have on aquatic ecosystems. Here, we test the hypotheses that the Ca limitations of Daphnia pulex (reduced growth/survival when Ca \1.5 mg L -1 ) identified in laboratory analyses and paleolimnological case studies can be observed among cladoceran assemblages from surface sediments alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 48 publications
2
24
0
Order By: Relevance
“…The dominance of pH suggests that zooplankton differ in their environmental tolerance ranges for pH, a finding noted elsewhere (Holt et al 2003), which has implications for community composition under the threat of lake acidification. Further, the impact of pH may also include the impact of other variables, as pH is often correlated with other water quality metrics such as calcium (Ca), dissolved organic carbon (DOC), and total organic phosphorus (Jeziorski et al 2012). The importance of DOC and pH to zooplankton communities is supported by previous analyses in boreal shield lakes influenced by acidification (Derry et al 2009).…”
Section: Discussionmentioning
confidence: 93%
“…The dominance of pH suggests that zooplankton differ in their environmental tolerance ranges for pH, a finding noted elsewhere (Holt et al 2003), which has implications for community composition under the threat of lake acidification. Further, the impact of pH may also include the impact of other variables, as pH is often correlated with other water quality metrics such as calcium (Ca), dissolved organic carbon (DOC), and total organic phosphorus (Jeziorski et al 2012). The importance of DOC and pH to zooplankton communities is supported by previous analyses in boreal shield lakes influenced by acidification (Derry et al 2009).…”
Section: Discussionmentioning
confidence: 93%
“…), due to the large amounts of Ca lost during each moult when the carapace is shed and subsequently regenerated (Alstad et al 1999). The dependence of cladocerans upon aqueous Ca availability has been demonstrated in both field surveys and examinations of present-day sedimentary remains that have identified lakewater Ca concentration as a significant explanatory environmental variable for cladoceran communities (Waervågen et al 2002;DeSellas et al 2008;Jeziorski et al 2012). The importance of aqueous Ca is likely due to speciesspecific differences in Ca requirements and Ca content (i.e.…”
Section: Introductionmentioning
confidence: 95%
“…In summer 2007, sediment cores were collected from the deepest basins of Young, Dunbar, and Oudaze lakes using a Glew (1989) gravity corer (Jeziorski et al, 2011). A Glew (1988) vertical extruder was used to extract the top 0.25 cm of sediment from each core, which in this region typically represents the last 0-3 years of sediment accumulation (e.g., Mills et al, 2009).…”
Section: Lake Selection and Field Methodsmentioning
confidence: 99%
“…D. catawba is an acidtolerant taxon that can thrive in low-Ca lakes (Cairns 2010), and is one of the most common daphniid taxa of the naturally acidic, low-Ca lakes of the Canadian Shield (Hebert & Finston, 1997). D. catawba has been observed to replace D. pulicaria in Plastic Lake (Muskoka, Ontario) when Ca concentrations declined (N. Yan, York University, personal communication), and Jeziorski et al (2011) identified coarse species resolution and differential species tolerances to low [Ca] to be detrimental to paleolimnological investigations on the response of daphniids to aqueous [Ca] decline. Furthermore, in areas such as Nova Scotia (Canada), where no long-term zooplankton monitoring datasets exist, our current understanding of how keystone daphniid communities have changed over time in response to acidification-related stressors relies solely on paleolimnological data (Korosi & Smol, 2011).…”
Section: Daphnia Pulex Complexmentioning
confidence: 95%
See 1 more Smart Citation